劍的雙面刃─國中數學科不同成就學生學習組型差異之分析 Double-Edged Sword: Different Learning Behavior Patterns for Junior High School Mathematics - 陳嘉成 Chia-Cheng Che; 陳柏霖 Po-Lin Chen; 洪兆祥 Chao-Hsiang Hung; 薛人華 Jen-Hua Hsueh (National Taiwan Normal University, 2018)
有些學生在資賦上很好，但學習表現卻不如預期，稱之為低成就學生；有些學生在資賦上低於平均數，但表現卻高於其能力水準，稱之為高成就學生。此兩類型學生剛好是能力與努力差異化的表徵。本研究目的係嘗試透過不同智力／成就組型的分析，來瞭解影響數學學習的相關心理機制，並嘗試探討數學教師能準確辨識低成就學生的比率與相關因素。本研究以 3,530 位國中學生為受試樣本，探討數學科低智商高成就與高智商低成就學生的學習行為構型。經由分析結果顯示：一、「低智商高成就」者占 5.6%、「低智商低成就」者占 4.1%、「高智商高成就」者占 9.5%、「高智商低成就」者占 10.2%；二、「數學能力知覺」與「自我設限」的學習組型可作為區分「低智商高成就」與「高智商低成就」的學生。最後，根據研究結果提出建議，以供教師及未來研究參考。 Some skilled students are deemed underachievers, even though they demonstrate adequate academic performances, because they fail to meet certain expectations. By contrast, some gifted students achieving below-average scores, but having performance capabilities exceeding their skill level, are labeled overachievers. These two categories representing student ability and effort have differences. This study investigated the profiles of underachievers and overachievers in junior high school mathematics by comparing variation patterns to build the foundation for future remedial education. Students from one junior high school were analyzed; the conclusions were as follows: (1) Of 3,530 participating students, 199 (5.6%), 143 (4.1%), 337 (9.5%), and 360 (10.2%) were low intelligence quotient (IQ) - overachievers, low IQ - underachievers, high IQ - overachievers, and high IQ - underachievers, respectively. (2) Perceived math competence and self-debilitating strategies were observed in high IQ - underachievers and low IQ - overachievers. (3) Finally, suggestions for teaching practices and future studies were proposed.